EFEKTIVITAS PELAKSANAAN PENGGUNAAN ALOKASI DANA DESA (ADD) DI DESA SETAKO RAYA KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Rahma Yulita; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Village Allocation Fund is a part of the central and regional equalization fund devoted to the village in implementing government services and community empowerment. Village Allocation Fund recived through rural development planning. But in reality the effectiveness of the implementation of the use is still not effective. In the implementation of the us the village allocation fund does not comply with the exixting policy, the human resources are still inadequate, the construction of facilies and infrastructure that had not been realized, Lack of the community participation. This studi aims to determine the effectiveness of the implementation of the us village allocation fund In the Setako Raya subdisctrict of the Peranap Indragiri Hulu.The concept of the theory that researchers use is organizational effectiveness by using Gibson’s theory by looking at the goals to be achieved clarity, clarity goal attainment strategy, process analysis and formulation of policy steady, careful planning, preparation of appropriate programs, availability of the insfrastructure and surveillance systems and control didactic. The researched method used is a qualititative researched study descriptive. In data collection, research using interview, observation and documentation stipulated by snowball samping.The result showed that the effectiveness of the implementation the use village allocation fund in the Setako Raya Subdisctrict of Peranap Indragiri Hulu has not been effective in the use of village allocation fund in not accordance with government policy. but it is still a lot of programs tha have not been implemented. As for the factors that influence that effectiveness of the implementation the use Village Allocation Fund in the Setako Raya subdisctrict of Peranap Indragiri Hulu the quality of human resources and coordination that has not been good.Keyword: Effectiveness, Implementation, Village Allocation Fund